2014
DOI: 10.7448/ias.17.4.19740
|View full text |Cite
|
Sign up to set email alerts
|

Rilpivirine versus etravirine validity in NNRTI‐based treatment failure in Thailand

Abstract: IntroductionEtravirine (ETR) and rilpivirine (RPV) are the second-generation non-nucleoside reverse transcriptase inhibitors (NNRTI) for treatment of HIV-1 infection. Etravirine is recommended for patients with virologic failure from first generation NNRTI-based regimen [1]. RPV has profile with similar properties to ETR but this agent is approved for treatment-naïve patients [2]. In Thailand, ETR is approximately 45 times more expensive than RPV. We aimed to study the patterns of genotypic resistance and poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Saravanan et al (2017), reported 47% and 65% ETR and RPV resistance profiles respectively, contrary to our current study which reported similar percentages of resistance profiles between ETR and RPV (both with 45.7% resistance). Teeranaipong et al (2014) reported 32.2 and 31.6% susceptibility in ETR and RPV, respectively which was in concordance with the results of this study. There is therefore a need for more studies to clearly define the prevalence of ETR and RPV-associated mutations in populations receiving first-generation NNRTIs especially sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Saravanan et al (2017), reported 47% and 65% ETR and RPV resistance profiles respectively, contrary to our current study which reported similar percentages of resistance profiles between ETR and RPV (both with 45.7% resistance). Teeranaipong et al (2014) reported 32.2 and 31.6% susceptibility in ETR and RPV, respectively which was in concordance with the results of this study. There is therefore a need for more studies to clearly define the prevalence of ETR and RPV-associated mutations in populations receiving first-generation NNRTIs especially sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 92%
“… 47 , 48 High prevalence of cross-resistance to etravirine (60%) has been reported in several studies of CRF01_AE-infected patients in Thailand for whom first-line NNRTI-based therapy was failing. 52 54 As efficacy data of etravirine use in south-east Asia are lacking, phenotypic assays investigating the in vitro susceptibilities of these clinical isolates would be helpful. Until then, etravirine and rilpivirine should probably be avoided as third-line drugs for patients infected with subtype CRF01_AE in south-east Asia.…”
Section: Discussionmentioning
confidence: 99%